Intrepretation of Metaphors in the Themes of Rewards and Punishments in the Holy Quran : A Cognitive-Semantic Approach - Khan, Sardaraz (unimas, 2017)
This study attempts to address the dichotomy of language and thought in the interpretation of metaphors in the themes of rewards and punishments in the Holy Quran. The rhetoricians and literary critics regard metaphor as a linguistic device, while the cognitive theorists consider it as a cognitive phenomenon. This dissociation between linguistic and conceptual knowledge is evident in metaphor interpretation in the themes of rewards and punishments in the Holy Quran. The former misses the experiential basis of metaphoric concepts, while the later ignore the pragmatic principles in metaphor interpretation of the Holy Quran. This study seeks to resolve the dichotomy of linguistic and conceptual knowledge in the interpretation of metaphors in the themes or rewards and punishments of the Holy Quran. It applies cognitive semantic approach, on the model of Lexical Concept and Cognitive Model (LCCM) theory along-with the tool of intertextuality, to the metaphors identified through metaphor identification procedure (MIP) in the data retrieved from the Arabic Quran with the help of technique of topical words and phrases. The findings reveal that metaphor has pervasively been used in the Holy Quran with systematic linguistic patterns which are occasionally overridden due to the idiosyncratic use of language. The constructive integration of linguistic and conceptual knowledge in the situational context offers not only the comprehensive interpretation and understanding of metaphors but also a systematic categorization of eschatological concepts. The findings of the study also reveal that intertextuality is a necessary tool not only for validation of interpretation but also for resolution of the different situational contexts in text interpretation